2014
DOI: 10.2298/vsp1404362z
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein E gene polymorphisms as risk factors for carotid atherosclerosis

Abstract: Our results suggest protective effect of apolipoprotein E epsilon2 allele on susceptibility for carotid plaque presence as well as low density lipoprotein cholesterol lowering effect in Serbian patients with carotid atherosclerosis. Further research of multiple gene and environmental factors that contribute to the appearance and the progression of atherosclerosis should be continued with respect to different populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…According to previous reports [ 37 , 38 , 39 , 40 ], the pathogeneses of NAFLD and atherosclerosis are both closely related to an imbalance of lipid metabolism. To explore the possible mechanism underlying the effectiveness of xyloketal B treatment of NAFLD, we investigated the effects of xyloketal B on lipid metabolism, mainly focusing on liver fatty acid synthesis and clearance pathways in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…According to previous reports [ 37 , 38 , 39 , 40 ], the pathogeneses of NAFLD and atherosclerosis are both closely related to an imbalance of lipid metabolism. To explore the possible mechanism underlying the effectiveness of xyloketal B treatment of NAFLD, we investigated the effects of xyloketal B on lipid metabolism, mainly focusing on liver fatty acid synthesis and clearance pathways in vivo and in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE can transport cholesterol and regulate lipid metabolism, and has become the focal point of recent studies (Al Harthi et al, 2014;Berkinbayev et al, 2014;Zurnić et al, 2014). In recent years, as the development of molecular biology and genetic engineering technologies has progressed, studies have demonstrated a close association between the ApoE gene polymorphism and serum lipid levels (Shin et al, 2014;Yin et al, 2014;Zhu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In total, there were 36,245 subjects (sample size ranging from 75 to 19,201) with 15,285 (42.2%) males and 20,960 (57.8%) female subjects. Geographically, three studies were conducted in the United States ( 13 , 24 , 25 ), two in Spain ( 16 , 26 ), one each in Japan ( 27 ), Australia ( 12 ), Poland ( 28 ), France ( 5 ), Taiwan ( 29 ), Turkey ( 30 ), Finland ( 31 ), Korea ( 32 ), the Netherlands ( 33 ), Greece ( 34 ), Italy ( 35 ), and Serbia ( 36 ). The majority were single-center studies, with three conducted at multiple sites ( 5 , 25 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
“…The majority were single-center studies, with three conducted at multiple sites ( 5 , 25 , 32 ). Six studies drew subjects from population samples ( 5 , 12 , 26 , 29 , 32 , 33 ) and the remaining studies evaluated specific populations including 1 study that sampled patients with coronary disease ( 16 ), one examined subjects after carotid endarterectomy ( 36 ), one looked at patients with chronic kidney disease on hemodialysis ( 27 ), one included post-transplant individuals ( 30 ), one with patients with ischemic stroke within seven days of onset ( 28 ), two evaluated males with hypertension ( 24 , 31 ), one had families with higher-than-expected rates of coronary heart disease ( 25 ), one enrolled menopausal women ( 34 ), and one examined mildly cognitively impaired individuals ( 35 ). Of the 17 studies in the systematic analysis, 10 were eligible for meta-analysis ( 5 , 12 , 13 , 16 , 25 27 , 29 , 32 , 33 ).…”
Section: Resultsmentioning
confidence: 99%